Canadian Cosmopoiesis: Meditations on Cuisine and Architecture - Frascari, Marco (Cuizine)

(untitled) (McGill University Library, 2009)
AbstractArchitecture and cuisine manifest themselves in the making; both evolve and last in the form of memories, tastes, and time, which generate cosmopoietic feats able to fashion signifying universes out of the sensual material of the world, and both are based on thinking with things rather than thinking about things. They are expressions of the human sapience for transforming terrestrial materials and products into edifying substances. They are both world-making expressions of a “maternal region” and, consequently, Canadian architecture can be understood through Canadian cuisine and Canadian cuisine through Canadian architecture.